Taksir Istikhdam At-taklim An-nasyath Nauun Rotating Roles Ala Maharah Kalam Lada Thalabah As-shaf As-tsamin Bi Madrasah As-tsanawiyah Al-ahliyah Lubuk Kilangan - Nur Rahmi (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
The purpose of this discussion is to determine the ability of speaking skills after using active learning type rotating roles in learning speaking skills. And to find out the effectiveness after using rotating roles type active learning in learning speaking skills for class VIII student at MTSs Lubuk Kilangan Padang. The approach used in this discussion is a quantitative approach. The research design is a quasi-experimental design in the form of a nonequivalent control design. And the data collection method used interviews, questions, and documentation. The form of data analysis that has been used by the author is the normality test,homogeneity test and T-test using SPSS 21. The results of this discussion are the students' ability in learning speaking skills of class VIII MTss Lubuk Kilang Padang students, before using the rotating roles method with the results of the pre test score in the control class 45.28 (accepted). And on the effectiveness of using the rotating roles method, it is known that there are differences in the value of speaking skills before and after. The value after using the rotating roles method is 71.55 (good). Judging from the graph table, the value before and after using the rotating roles method in the experimental class has increased from an acceptable value to a good value. This means that the use of active learning types of rotating roles has an effect on the speaking skills of class VIII students at MTSs Lubuk Kilangan Padang